Estudo da anisotropia unidirecional e da histerese rotacional em sistemas com exchange bias - Rigue, Josué Neroti (2014)
The exchange bias (EB) phenomen occurs due to the coupling between ferromagnetic and antiferromagnetic material and the main characteristics are the rise of unidirectional anisotropy and the rotational hysteresis in torque curves. In this work we have investigated how the unidirectional anisotropy and the rotational hysteresis are influenced by the change of some characteristics in thin films samples. Among these are the stacking of layers, the roughness at the interface between the two materials, the difference in the ferromagnetic layer thickness and the difference between the antiferromagnetic materials. The study was made by using magnetic torque measurements which were interpreted using a granular model for the EB. The parameters obtained from the fitting of the model to the torque curves has also permitted to reproduce data obtained by different magnetic techniques, especially in samples where the unidirectional anisotropy is greater than the uniaxial anisotropy. In NiFe=IrMn samples, the unidirectional anisotropy is favored by stacking layers, by increasing of the interfacial roughness and by the decrease of the ferromagnetic layer thickness, while the rotational hysteresis is substantially increased as the interfacial roughness increases. For the NiFe=FeMn sample the highest values of unidirectional anisotropy and rotational hysteresis were found, as well as a dependence of these parameters with the measuring magnetic field.